Elements of Fiction as a Communicative Resource in Activism: Analysis of the (audio)visual content on social media - Balaguer, Juanjo; Gifreu-Castells, Arnau (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
The article proposes a study of the elements of fiction as a communicative resource in the context of contemporary activism. To this end, the analysis encompasses the examination of visual and audiovisual content published by Greenpeace and Extinction Rebellion on X and Instagram over a six-month period. The research has identified a series of categories that articulate these fictional elements, namely the meme, the comic, the performance, the short video, and the animated video. Finally, the article presents conclusions regarding the use of fiction, which is frequently associated with references to mainstream culture.